Self-control and impulsiveness before and during the pandemic. A comparative study to evaluate possible changes in different age groups - Brenlla, María Elena (2023)
This article describes and compares the levels of self-control and impulsivity, key aspects of self-regulation, in three age groups to evaluate possible differences due to age; and at two times: September 2019 (n=190), a normal period, and September 2020 (n=199), a period with lockdown during the pandemic. It was found that self-control increases, and impulsivity decreases with increasing age. Also, improvidence impulsivity was higher during the pandemic, while compulsive urgency and self-control were lower than in 2019. In short, age is a relevant factor in explaining differences in self-regulation, and the COVID-19 restrictions led to a depletion of self-control and greater impulsivity in times of stress.